Pathological features of glomerulonephritis in Jakarta (Faculty of Medicine Universitas Indonesia, 2002)
All cases of renal biopsies received during a 10-year period from 1990-1999 were collected and analyzed. There were a totat of 1344 cases, comprising 390 pediatric cases, 9 I 8 adult cases and 36 cases of unknown age. Immunofluorescence microscopy was performed on 1089 cases (81.0%). The purpose of this study is to have an overview of the pattem and spectrum of glomerular diseases in Indonesia, especially in Jakarta and surroundings, with special emphasis on the cases with nephrotic syndrome, lupus nephritis and IgA nephropathy, and to compare the findings with previous reports from Indonesia and afew other countries. There were 250 cases of childhood nephrotic syndrome and 479 adult cases. The most frequent histopathological appearance in both groups was minimal change disease, i.e. 58.2% and 44.7% respectively. Males were more often affected than females with a ratio of 2.0:1 for children and 1.4:1 for adults. Lupus nephritis comprised 124 cases, among which three cases were not representative. The male to female ratio was 1:7.9. Most cases were in the fourth decade, i.e. 47 cases (38.5%), and the most frequent histopathological appearance was WHO class IV with 71 cases (58.7%). There were 97 cases of IgA nephropathy with an age range between 3 to 58 years. The peak incidence was in the fourth decade with 32 cases (33%). The male to female ratio was L7: I. The most frequent histopathological appearances were diffuse sclerosing lesion 34 cases (35%) and mesangial proliftrative lesion 33 cases (34%). (Med J Indones 2002; 11: 24-9)Keywords: renal biopsy, pathological features, glomerulonephritis, nephrotic syndrome, lupus nephritis, IgA nephropathy